Improving nutrition care for neurosurgery patients through a nurse‐led transition feeding protocol. Issue 2 (13th March 2019) - Dux, Claire; Lim, Shu‐Chuin; Jeffree, Rosalind; Heaydon, Sandra; de Jersey, Susan
Abstract : Aim: Neurosurgical patients often transition from enteral nutrition (EN) to oral nutrition (ON) as they recover. Implementing a nurse‐led feeding protocol to guide this transition may improve consistency of nutrition care and dietitian workload efficiency. This pragmatic study aimed to evaluate the effect of such a protocol on these outcomes and on nurses' nutrition care attitudes, practices and knowledge. Methods: Data were collected retrospectively for 1 year pre‐ and prospectively for 1 year post‐implementation of the transition feeding protocol (TFP). Participants who transitioned from EN to ON were included in the study. Post‐implementation nurses in the neurosurgery ward were invited to complete a self‐administered questionnaire to investigate attitudes, practices and knowledge. Results: One hundred and thirteen participants, 55 pre‐ and 58 post‐implementation, took part in the study. Significantly more patients received transition feeding (TF) post‐implementation (58% vs 93%, P < 0.001), there was a statistically significant improvement in the commencement of TF (0 vs 1 day after ON clearance; P = 0.029), and all patients consumed adequate oral intake 1‐week post‐EN cessation (92.3% vs 100%, P = 0.078). There was no difference in dietetic occasions of service post‐implementation (2 vs 1.5; P = 0.204). A 38% survey response rate from nursing staff (n = 15) was achieved. More nurses were found to be initiating TF ( P < 0.001) and a majority reported a perceived increase in knowledge and confidence in providing nutrition support. Conclusions: A TFP can optimise the transition from EN to ON by improving consistency and commencement of TF and nurses' confidence and knowledge in overall nutrition care.